On the polyamorphism of fullerite-based orientational glasses - Aleksandrovskii, A.N.; Moricca, S.; Manzhelii, V.G.; Gavrilko, V.G.; Gadd, G.E.; Esel`son, V.B.; Dolbin, A.V.; Cassidy, D.; Bakai, A.S.; Sundqvist, and B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
The dilatometric investigation in the temperature range of 2–28 K shows that a first-order polyamorphous transition occurs in the orientational glasses based on C60 doped with H2, D2 and Xe. A polyamorphous transition was also detected in C60 doped with Kr and He. It is observed thatthe hysteresis of thermal expansion caused by the polyamorphous transition (and, hence, the transitiontemperature) is essentially dependent on the type of doping gas. Both positive and negative contributions to the thermal expansion were observed in the low-temperature phase of the glasses. The relaxation time of the negative contribution occurs to be much longer than that of the positive contribution. The positive contribution is found to be due to phonon and libron modes, whilst the negative contribution is attributed to tunneling states of the C60 molecules. The characteristic time of the phase transformation from the low-T phase to the high-T phase has been found for the C60–H2 system at 12 K. A theoretical model is proposed to interpret these observed phenomena.The theoretical model proposed, includes a consideration of the nature of polyamorphism in glasses, as well as the thermodynamics and kinetics of the transition. A model of noninteracting tunneling states is used to explain the negative contribution to the thermal expansion. The experimental data obtained is considered within the framework of the theoretical model. From the theoretical model the order of magnitude of the polyamorphous transition temperature has been estimated. It is found that the late stage of the polyamorphous transformation is described well by the Kolmogorov law with an exponent of n = 1. At this stage of the transformation, the two-dimensional phase boundary moves along the normal, and the nucleation is not important.